"An example for corporate social responsibility": British American Tobacco's response to criticism of its Myanmar subsidiary, 1999–2003. Issue 2 (26th April 2018) - MacKenzie, Ross
Abstract: In 2013, British American Tobacco (BAT) returned to Myanmar a decade after it had left the country under pressure from civil society, international organizations, and the government of the United Kingdom. The company's involvement in a joint venture with an investment branch of the country's military government between 1999 and 2003 resulted in intense scrutiny and criticism based on the military's record of human rights abuses. BAT argued that corporations could not be held accountable for actions of governments in countries in which it operated, and that its presence in Myanmar contributed to economic and social development. It also maintained that its Myanmar subsidiary provided a model of responsible business conduct. The controversy that surrounded BAT's Myanmar subsidiary between 1999 and 2003 has increasing relevance to the current situation in Myanmar, and potential implications for foreign corporations operating in the country.